2022
DOI: 10.36253/a_h-10188
|View full text |Cite
|
Sign up to set email alerts
|

First report on two loggerhead turtle (Caretta caretta) nests in the Aeolian Archipelago (Southern Italy)

Abstract: The Aeolian Archipelago (Southern Tyrrhenian Sea, Italy) hosts important foraging/overwintering habitats for Mediterranean loggerhead sea turtles (Caretta caretta), although nesting sites have never been documented. This study reports the data of two nesting events occurred in summer 2019 at Stromboli and Lipari islands. A hatchling success of 20.69 % (18 hatchlings from 87 eggs) was recorded at Stromboli, while a complete hatchling unsuccess characterised the Lipari nest, where 111 eggs were deposited. Data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…While increasing awareness and reporting by citizens may partially explain the increasing records of nesting events, the long absence of nesting events followed by almost yearly events between 2018 and 2023 clearly indicates an increasing trend in nesting activity around this archipelago. A trend similar to that noted in the Western Mediterranean, where, during the last decade, C. caretta has been expanding its nesting range and increasing nesting events in the region [6,7,86], possibly in response to global warming [7].…”
Section: Discussionsupporting
confidence: 74%
“…While increasing awareness and reporting by citizens may partially explain the increasing records of nesting events, the long absence of nesting events followed by almost yearly events between 2018 and 2023 clearly indicates an increasing trend in nesting activity around this archipelago. A trend similar to that noted in the Western Mediterranean, where, during the last decade, C. caretta has been expanding its nesting range and increasing nesting events in the region [6,7,86], possibly in response to global warming [7].…”
Section: Discussionsupporting
confidence: 74%
“…Many factors, particularly anthropic, threaten the conservation of this species during the juvenile and adult ages at sea and the spawning period and embryonic development in coastal nesting areas. The sea and beach pollution, overbuilding, and degradation of the coastal areas, tourism, climate change, presence of predators, rains, floods, and microbial infections are compromising factors for both hatching and survival rates of the newborn [ 1 – 10 ]). To date, there is an increasing interest in microbial community studies to provide information on the ecology of the host and improve conservation efforts, rescue, and rehabilitation practices.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such information is not very useful as it is often unreliable and lacking essential information. Conversely, scientific papers dealing with this topic appear to date rather limited (e.g., Blasi et al, 2022;Denaro et al, 2022;Vecchioni et al, 2022a;Vecchioni et al, 2022b). Recently, Hochscheid et al (2022) have shown that from 2010 to 2023 in the western sector of the Mediterranean Caretta caretta has shown a progressive expansion of the nesting area, as evidenced by the occurrence of a high number of nests in areas where the females had never been known to lay eggs before.…”
Section: Introductionmentioning
confidence: 99%